Pengaruh Model Pembelajaran Cooperative Script Terhadap Kemampuan Berpikir Kreatif Peserta Didik Mata Pelajaran IPAS Kelas IV di Sekolah Dasar - Anggara, Jeky Septa; Amrina Izzatika; Niken Yuni Astiti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine whether the Cooperative Script learning model has an effect on students’ creative thinking skills in the IPAS subject for fourth-grade students at SDN 1 Metro Timur. The method used in this study is a quasi- experimental method (quasi-experimental design) with a non-equivalent control group design. The sampling technique was carried out by a non-probability sampling method with a saturated sampling technique. The population in this study was 50 students, with class IV A as the control group and class IV B as the experimental group. Data collection techniques were carried out through tests and non-tests. Data analysis used a simple linear regression test. The results showed that there was an influence of the Cooperative Script learning model on students' creative thinking abilities in the subject of Science, as evidenced by the significance value in the ANOVA table, namely 0.000 <0.05 and the t-value of 3.43 which was greater than the t-table, namely 2.080.